Exaggerated arsenic nephrotoxicity in female mice through estrogen-dependent impairments in the autophagic flux. (2nd January 2016) - Kimura, Akihiko; Ishida, Yuko; Nosaka, Mizuho; Kuninaka, Yumi; Hama, Mizuki; Kawaguchi, Takashi; Sakamoto, Shoichi; Shinozaki, Kohei; Iwahashi, Yumi; Takayasu, Tatsunori; Kondo, Toshikazu
Abstract: Gender is one of the essential factors in the development of various diseases and poisoning. Therefore, we herein examined gender differences in sodium arsenite (NaAsO2 )-induced acute renal dysfunction. When male and female BALB/c mice were subcutaneously injected with NaAsO2 (12.5 mg/kg), serum and urinary markers for proximal tubular injury were significantly higher in female mice than in male ones. NaAsO2 -induced histopathological alterations were consistently more evident in females than in males. Ovariectomy, but not orchiectomy significantly attenuated NaAsO2 -induced renal injury. These results imply that the hypersusceptibility of female mice is attributed to estrogen signals. NaAsO2 suppressed the autophagic flux in tubular cells through the activation of ERK. Enhancements in the activation of ERK were significantly greater in females than in males, with the eventual accumulation of LC3-II and P62 in the kidneys, implying that the autophagic flux is impaired in females. The IL-6/STAT3 signaling pathway had protective roles in NaAsO2 -induced nephrotoxicity through the suppression of ERK activation. Despite the absence of differences in intrarenal IL-6 expression between male and female mice, STAT3 was less activated with enhanced SOCS3 expression in females than in males. An in vitro study using mProx24 cells revealed that the estrogen treatment induced SOCS3 expression, and eventually suppressed the autophagic flux, as evidenced by greater increases in the accumulation of LC3-II and p62 with ERK activation, which was canceled by the knockdown of Socs3 . Collectively, these results indicate that estrogen has a negative impact on the development of NaAsO2 nephrotoxicity through its suppression of the autophagic flux.